Divine Resistance: Hezbollah’s Theocratic Duality of Politics and Military Power - Zafar, Sheikh Arslan; Akhtar, Dr. Humera (Journal of Political Studies, 2025)
Backing Hezbollah and deterring Israel," shields are viewed as protecting Lebanon’s interests and security. The "Resistance's Arms" Discourse: Hezbollah has effectively positioned its armed faction not as an uncontrolled militia, but as an essential national defense entity against Israel. This study examines how Hezbollah's actions, influenced by Iran’s Wilayat al-Faqih doctrine, shape Lebanon’s security and political landscape. By aligning with Iran’s regional goals, Hezbollah defends Lebanon while promoting Shiite interests, including military activities near Beirut. The research explores Hezbollah’s multifaceted role as both a political party and an armed organization supported by Iran’s Islamic Revolutionary Guard Corps (IRGC), and its impact on Lebanon's sovereignty and regional stability. It also looks at Hezbollah’s evolution from a resistance movement to a significant political force. This study also discusses Hezbollah’s dual role and how Iran's leadership influences its actions, aiming to protect Lebanon and support the broader Shiite cause. Theocratic political theory is used as a framework to analyze Hezbollah’s connection with Iran and its influence on Lebanon's internal stability. Ultimately, the study recommends including Hezbollah in Lebanon’s political and military structures to reduce potential instability while balancing national unity and regional interests.